Nurses, Chaplains, Clergy and Measurement Scales - Carey, Lindsay B. (Journal of religion and health, 2025)
Much of the research in this issue relates to the long-standing profession of nursing and, secondly, the even longer established professions of chaplaincy and the clergy. This issue also provides evidence of the ever-increasing number of religious and spirituality measurement scales, as well as various other forms of religious and/or spiritual evaluations and the associated psychometric properties. Several articles researching religiosity/spirituality, however, identify common research limitations, in particular the error of using contaminated scales and the need to avoid tautological and uninterpretable results. Finally, this issue notes two international conferences for 2025 relating to religion, spirituality and health.